ANÁLISE DOS ELEMENTOS DETERMINANTES NA APROPRIAÇÃO DE VALOR NAS INOVAÇÕES DA AGRICULTURA FAMILIAR NA CIDADE DE GUARAPUAVA-PR - BAGGIO, CLAITON ALORENUS (2017)
Smallholder agriculture is an important segment of agribusiness, since it covers the vast majority of farmers that work in agriculture. This sector faces difficulties that threaten its competitiveness, such as the historical downward trend of price of agricultural products, the difficulty of achieving cost reduction through a gain of scale due to the restriction of production area and the lower bargaining power in marketing because of its small size. In this scenario, innovation is important to achieve lower costs and better production quality. But only innovating is not enough, frequently the value created with innovation is totally appropriate by others in the network, which nullifies the results of these investments to the farmer. Teece (1986), when analyzing the appropriation of value of innovations, proposed a widely accepted model that aims to ascertain what the determining factors for value appropriation with innovation are. Based on this model and in related studies, it was sought to analyze the determining factors for the appropriation of the value of innovations in smallholder agriculture. For this, a quantitative survey was carried out with family farmers from Guarapuava-Pr, with the objective of analyzing how they access the determinants to the value appropriation with innovation. The analysis of how family farmers position themselves on the determinant factors to appropriate value with innovation contributes to support more assertive strategies for this segment. The results indicate that the vast majority of farmers do not develop the determinants to take ownership of the value created with innovation. As a data collection instrument, the structured questionnaire was used, which was answered by 199 family production units. Data analysis was based mainly on descriptive analysis and by means of correlation test and hypothesis test. The access to government programs aimed at commercialization and cooperativism, have demonstrated a relation with the determining factors for the appropriation of innovation. The form of operation in the chain also showed positive correlation with the determinants of value appropriation with innovation. Another important result is the finding that smaller smallholders tend to innovate more frequently in product and market than others. The work contributes both theoretically and in a practical way when seeking the understanding of the mechanisms of value appropriation with the innovation of this activity in an evolutionary perspective. Information obtained bring subsidies for farmers find ways to achieve better results in their innovations. The study also demonstrates the importance of making innovations, accessing complementary assets adequately and adapting to changes, due to the pressures of the evolutionary environment.